2019
DOI: 10.1001/jamanetworkopen.2019.4900
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors at Index Hospitalization Associated With Longer-term Mortality in Adult Sepsis Survivors

Abstract: Key Points Question Which generic and sepsis-specific patient characteristics, known during index critical care admission for sepsis, are independently associated with long-term mortality in sepsis survivors? Findings In this cohort study of 94 748 adult sepsis survivors, age, male sex, 1 or more severe comorbidities, prehospitalization dependency, nonsurgical status, acute severity of illness, site of infection, and organ dysfunction were independently ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
75
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 78 publications
(86 citation statements)
references
References 42 publications
6
75
1
4
Order By: Relevance
“…The 1-year mortality rate among sepsis survivors in the present study is within the range previously reported in the literature. 9,16,36 Shankar-Hari et al 16 and Yende et al 36 recently reported 1-year mortality rates of 15% and 17.6%, respectively, among relatively young and previously healthy patients with few comorbidities and high rates of prehospital functional independence. In contrast,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1-year mortality rate among sepsis survivors in the present study is within the range previously reported in the literature. 9,16,36 Shankar-Hari et al 16 and Yende et al 36 recently reported 1-year mortality rates of 15% and 17.6%, respectively, among relatively young and previously healthy patients with few comorbidities and high rates of prehospital functional independence. In contrast,…”
Section: Discussionmentioning
confidence: 99%
“…The present study's results support previous reports of older age, male sex, medical admission type, comorbidities, and cancer in particular, being important risk factors for long-term mortality after sepsis. 16,38 Additional sepsis-related risk factors were identified, including severe sepsis, respiratory infection source, and ICU use. Such information may be useful to guide future efforts to develop and test risk stratification models among sepsis survivors, which may facilitate tailoring…”
Section: Discussionmentioning
confidence: 99%
“… 1 We have previously reported 5-year mortality outcomes in this sepsis survivor cohort. 8 Unplanned rehospitalization episodes and rehospitalization diagnoses were ascertained from the linked data set and grouped as per the Healthcare Cost and Utilization Project Clinical Classifications Software multilevel categories. 17 This mapping was similar to previous reports in the literature.…”
Section: Methodsmentioning
confidence: 99%
“…The derivation cohort included all consecutive admissions between April 1, 2009, and March 31, 2014, with the date of rehospitalization or death ascertained as of March 31, 2015. 8 The validation cohort included all consecutive admissions between April 1, 2014, and March 31, 2015, with the date of rehospitalization or death ascertained as of March 31, 2016. This validation cohort meets the temporal (narrow external) validation definitions in the TRIPOD statement 12 because it uses the same predictors, the same outcome definitions, and the same measurements from the same setting, but sampled from a later period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation